1993
DOI: 10.1080/02652039309374170
|View full text |Cite
|
Sign up to set email alerts
|

Calculated Dietary Intakes of Nitrate And Nitrite By Young Finns

Abstract: Dietary intakes of nitrate and nitrite of 1212 Finns aged 9, 12, 15, 18, 21, and 24 years were calculated using food consumption data obtained by the 48-hour recall method in 1986, in connection with the Study on Cardiovascular Risk in Young Finns. Files on nitrate and nitrite content of foods and water were compiled for this study. The mean daily intakes of nitrate (NO3-) and nitrite (NO2-) from food were 54.0 mg and 1.4 mg, respectively. Vegetables including potatoes contributed 86% of nitrate intake and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Nitrate (NO 3 − ) is white crystalline powder and also naturally occurring compounds present in various form in the environment. It has been also proved that nitrates present in fruits and vegetables [30] , [42] . WHO recommended that the daily intake (ADI) for nitrate should be 3.67 mg/kg body weight and for nitrite it must not be greater than 0.13 mg/kg body weight (WHO, 1973) because higher concentration of nitrates has caused cancer in adults and increased the possibility of brain tumour, leukaemia, and nasopharyngeal [50] , [8] .…”
Section: Introductionmentioning
confidence: 96%
“…Nitrate (NO 3 − ) is white crystalline powder and also naturally occurring compounds present in various form in the environment. It has been also proved that nitrates present in fruits and vegetables [30] , [42] . WHO recommended that the daily intake (ADI) for nitrate should be 3.67 mg/kg body weight and for nitrite it must not be greater than 0.13 mg/kg body weight (WHO, 1973) because higher concentration of nitrates has caused cancer in adults and increased the possibility of brain tumour, leukaemia, and nasopharyngeal [50] , [8] .…”
Section: Introductionmentioning
confidence: 96%
“… Sang et al (2019) found that the contribution rates of drinking water and food sources accounted for 0.08 and 0.69% of endogenous NDMA in Chinese subjects. Endogenous NDMA also arises from the formation of NDMA in vivo from the consumption of meat and bacon cured with nitrite, nitrate-rich vegetables and seafood ( Laitinen et al, 1993 ; Dich et al, 1996 ; Zeilmaker et al, 2010 ). Post-mortem study of human subjects showed that endogenous NDMA is found in all tissues, including the brain ( Cooper et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…Este valor varia de acordo com os hábitos alimentares característicos de cada região. LAITINEN et al (1993) revelaram que 86% da ingestão de nitrato (NO 3 -) pelos finlandeses advêm dos vegetais, com um consumo diário de 54 mg de NO 3 -por pessoa.…”
Section: Introductionunclassified